TINDAK TUTUR ILOKUSI PADA NOVEL SI ANAK CAHAYA KARYA TERE LIYE - Anisa Rahmwati; Patriantoro Patriantoro; Ahmad Rabi’ul Muzammil (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe illocutionary speech act is expression to say or inform something with a specific purpose and function. This study aims to prevent speaker and interlocutor from misunderstand the meaning of a speech. The researcher chose illocutionary speech act as the research focus to describe each classification in this study. The researcher chose a novel because it shows about daily basis. This research used descriptive method in the qualitative approach with documentary. The source is from “Si Anak Cahaya” by Tere Liye, which are sentences and conversations. The researcher as the key instrument and uses it into reading results that included illocutionary speech acts in the novel. The data validity was carried out by two analysis, namely observation persistence and reference coverage. The results showed that there are 87 expressions, divided into 41 assertive, 22 directive and 18 expressive illocutionary speech acts. Based on the results, the conclusion is assertive illocutionary speech acts are more than the others. Declarative and commissive illocutionary speech acts are not found in the novel because they are typical speech acts that done by authority person in a certain institution.Keywords: Illocutionary speech act, novel